New strategies towards reversible and mendable epoxy based materials employing [4πs + 4πs] photocycloaddition and thermal cycloreversion of pendant anthracene groups. (2nd December 2015) - Radl, Simone; Kreimer, Manuel; Griesser, Thomas; Oesterreicher, Andreas; Moser, Andreas; Kern, Wolfgang; Schlögl, Sandra
Abstract: The present study highlights the design of reversibly crosslinkable epoxy based materials that undergo well-defined bond formation and bond cleavage in response to external stimuli. In this approach the controlled crosslinking relies on the highly reversible nature of [4πs + 4πs] cycloaddition reactions of anthracene derivatives. New epoxy monomers are synthesized which bear reactive anthracene groups that enable the formation of crosslinked networks due to concerted photocycloaddition reaction. A subsequent heating to temperatures up to 130 °C leads to thermally induced cleavage of the photodimers again. The crosslink kinetics as well as the reversible bond formation of the new epoxy based resins are characterized by spectroscopic techniques and dynamic mechanical analysis. Along with the reversible network characteristics, the new epoxy based materials promote intrinsically healable material properties since the photodimers are mechanochemically cleaved upon crack insertion. In fluorescence micrographs the evolution of a strong fluorescence emission along the crack planes is observed which can be related to the regeneration of the original anthracene groups in the damage-zone. Repair of the macroscopic cracks across the restored anthracene groups is achieved upon re-irradiation with UV-light (λ > 300 nm) and simultaneous heating at temperatures which are above the glass transition temperature of the epoxy based materials. The ability of the new materials to restore their mechanical properties after a repeated inflicting of macroscopic cracks at the same fracture point is confirmed by three-point bending tests. Load-displacement curves reveal that in terms of force at break the reversibly crosslinkable networks promote healing efficiencies between 84 and 100% after the first repair step. Graphical abstract: Highlights: Synthesis of new epoxy monomers that bear reactive anthracene moieties. Design of mendable epoxy based materials using reversible cycloaddition reactions. Reversible network characteristics are studied by UV–Vis and DMA measurements. Repair process involves UV exposure (λ > 300 nm) and simultaneous heating at 60 °C. Healing efficiencies between 84 and 100% are obtained after the first repair step.